Innovative Design and Application of Pitching Movement Transmission Mechanism in Large-scale Wind Tunnel - Guangfei You; Dewei Zhang; Zhihui Lu; Guoliang Zheng; Yongqiang Qiao; Yanbo Lai (Jixie chuandong)
Aiming at the design difficulties of the key motion mechanism of the model supporting mechanism in the large-scale wind tunnel test， this manuscript proposes a new linear actuation transmission mode based on circular arc motion from the perspective of engineering practicality. This mode realizes the linear actuation function with a limited range of rotation， and overcomes the problems of high manufacturing cost and difficulty in installation and commissioning of large-size and high-precision worm gear pair in the past. To verify the effectiveness of this mode， a comprehensive analysis of the mechanism from aspects of dynamics of mechanism， kinematics of mechanism， control characteristics， stiffness and strength is conducted. At present， the design of the pitching movement transmission mechanism has been applied to the model mechanism of a large wind tunnel. The wind tunnel model has a pitch angle displacement range of 45°， and the radius of the circular motion reaches 2 800 mm. The integrated model features low cost and is easy to maintain.